Czy chłopom w Prusach żyło się dobrze? (XVIII w.) = Did peasants live well in the 18th century Prussia? - Łukasiewicz, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
When compared with the 19th and 20th c. historical reports, the image of Polish peasants` life and their relations with the 18th century court, as we know today, has significantly improved, and the primary sources do not prove otherwise. Many historians are still critical as regards familiar and paternal relations between the gentry and peasants, but it remains to be established whether their assumptions are well-grounded.
Keywords: folwark; poddaństwo; własność królewska; ziemniaki; nieurodzaj; grange; serfdom; royal property; crop failure; potatoes